Drawn‐on‐Skin Sensors from Fully Biocompatible Inks toward High‐Quality Electrophysiology. Issue 36 (19th February 2022) - Patel, Shubham; Ershad, Faheem; Lee, Jimmy; Chacon‐Alberty, Lourdes; Wang, Yifan; Morales‐Garza, Marco A.; Haces‐Garcia, Arturo; Jang, Seonmin; Gonzalez, Lei; Contreras, Luis; Agarwal, Aman; Rao, Zhoulyu; et al.
Abstract: The need to develop wearable devices for personal health monitoring, diagnostics, and therapy has inspired the production of innovative on‐demand, customizable technologies. Several of these technologies enable printing of raw electronic materials directly onto biological organs and tissues. However, few of them have been thoroughly investigated for biocompatibility of the raw materials on the cellular, tissue, and organ levels or with different cell types. In addition, highly accurate multiday in vivo monitoring using such on‐demand, in situ fabricated devices has yet to be done. Presented herein is the first fully biocompatible, on‐skin fabricated electronics for multiple cell types and tissues that can capture electrophysiological signals with high fidelity. While also demonstrating improved mechanical and electrical properties, the drawn‐on‐skin ink retains its properties under various writing conditions, which minimizes the variation in electrical performance. Furthermore, the drawn‐on‐skin ink shows excellent biocompatibility with cardiomyocytes, neurons, mice skin tissue, and human skin. The high signal‐to‐noise ratios of the electrophysiological signals recorded with the DoS sensor over multiple days demonstrate its potential for personalized, long‐term, and accurate electrophysiological health monitoring. Abstract : Sensors fabricated directly on the skin are extremely promising for customized, on‐demand, and high‐quality physiological monitoring. However, the current literature does not thoroughly investigate the biocompatibility of the raw electronic materials deposited on skin. The development of a drawn‐on‐skin ink that is biocompatible on the cellular, tissue, and organ levels and can be used for multiday, high‐fidelity electrophysiology is presented.